Sound radiation produced by a ship propeller - KOZACZKA, Eugeniusz (Archives of Acoustics, 1979)
The theory of the generation of acoustic radiation by a ship propeller working in a stream with a non-uniform stationary distribution is briefly discussed in this paper. Relations permitting calculation of acoustic pressure values produced by a ship propeller working under given conditions are also derived. The acoustic method for determining the coefficients characterizing the load variation of ship propeller blades working in a non-uniform liquid stream with stationary characteristics is also discussed. This method can also be used for estimation of the velocity field non-uniformity for the flow of the medium in which the propeller works. Experimental measurements were carried out and calculations made, based on the equations derived, and the values were compared. Numerical computations were made, based on purpose-designed programmes. Spectral analysis was carried out numerically using an FFT algorithm.